Initial research protocol for re-using and re-analysing GENNOVATE data - Lopez, Diana E.; Rietveld, Anne (2024)
To allow re-using the GENNOVATE data for purposes distinct to those from the original research objectives and for re-analysing the GENNOVATE data, an anonymized derived dataset was developed. This includes 108 case studies from 23 GENNOVATE countries.